TECTONOSTRATIGRAPHY OF OFFSHORE WEST TIMOR: ITS IMPLICATION TO THE SAND RESERVOIR DISTRIBUTION OF PLOVER FORMATION - Sativa, Ludi
Offshore West Timor is a frontier area with complex structural framework as a result of collision between Banda arc and Northern Australian continental margin. The previous research within the area were mainly foccused on the island of Timor and are very few compare to the neighboring Timor Leste and Australia. The objectives of this study are to understand the tectonostratigraphic framework and to highlight the structural evolution based on the updated subsurface data in offshore West Timor. Tectonostratigraphic analysis will be useful to predict the distribution of Plover sandstone that is the main reservoir, as well as to predict the potential trap for hydrocarbon accumulation in Timor. Approximately 3,000 km semi-regional 2D seismic which were tied to five wells in offshore West timor have been interpreted to identify series of stratigraphic units with refers to the tectonic events. Seismic stratigraphy approach is required because of well control limitation in Offshore West Timor. Onshore Timor Geological Map has been incorporated with the subsurface data in order to establish facies map of Plover sandstone that is the main reservoir in Timor. The result of seismic interpretation suggest that the structural evolution in Timor controlled significantly by the collision between Australian Continent and Banda fore-arc. In the pre-collision stage, the research area was part of the northern Australian Continent consists dominantly of northeast-southwest trending normal faults. The Late Miocene collision result in thrust-fold belt complex with east northeast- west southwest trend. A regional cross section shows that the thrust fault model is thick-skinned in onshore Timor and thin-skinned in offshore Timor Sea. The detachment of thin-skinned thrust is on the shale of Wailuli Formation. In the thrust front, the isopach map indicate a thickening of Pliocene – recent sediment which represent character of foreland basin. However, the structures formed in front of the thrust-fold complex during collision are extensional type. This deformation results in reactivation of the older Mesozoic normal faults, and the creation of new normal faults in the shallow levels with east northeast – west southwest orientation. The presence of extensional deformation in front of the foreland might be explained due to flexure of the loading resulted from the thrust fault in Timor. The isopach map coming from seismic interpretation suggest the thickening of Early Triassic to Late Jurassic interval within the northeast – southwest graben. This thickening indicates the rifting phase in Northern Australian continent during Early Triassic to Late Jurassic. Early Cretaceous to Late Miocene interval characterized by a relative constant thickness from isopach map and overlay unconformably above the Jurassic or Triassic sequence. This interval represents the post-rift sedimentation in passive margin tectonic setting. Furthermore, the Pliocene to recent interval consists of syn-orogenic deposit due to collision between Australian Continents with the Banda fore-arc. The subsurface map and paleogeographic map of the Early to Middle Jurassic interval suggest that the distribution of the Plover sandstone controlled by Triassic to Jurassic normal faults, Late Jurassic regional unconformity, and type of depositional environment. Sandstone of Plover Formation widely distributed in offshore Timor, and eroded in most part of Ashmore Platform. In onshore Timor, the facies changes become shale of Wailuli Formation. In the thrust-fold complex, potential trap for Plover sandstone is sub-thrust structure, includes combination fold & fault and tilted fault block. Meanwhile in the foreland, the potential trap might be divided into structural and stratigraphic traps. The structural traps include tilted fault block and combination fold & fault. The stratigraphic trap is a sub-unconformity, which indicated by the truncation feature at the crest of reservoir.